Psycholinguistic Study: Indonesian Language Acquisition in Children Aged 0-2 Years - Eksawati, Lutfi; Dinata, Sigit Andi Prasetya; Warohmah, Winda (Universitas Sebelas Maret, 2023)
This study examines the acquisition of phonologyiand morphologyiin childreniage 0-2 yearsithe peopleihis parents communicate usingiIndonesianiin everyday life, while the surrounding environment uses the regional language (Javanese). ResearchiThis states that language development in children can vary between individuals, with different rates of development, which are influenced by age factors, parental abilities, and the active role of the environment in supporting development. This type of research is descriptive research.iqualitative where the data produced is in the form of oral speech which is then transcribed into written form. The method applied in collecting data related to phonological acquisitioniand morphologyionichildren aged 0-2 yearsicovers a wide rangenapproach.nResultsifromistudyiThisiexpectedncaniprovide a deeper understanding ofnFactors that influence children's language acquisition in the early stages of their development.